Effect of governance and foreign aid on poverty eradication - Kuek, Ming Shuen (2023)
According to the Sustainable Development Goal 1 (SDG 1), the United Nations (UN) aims to eliminate extreme poverty by the year 2030. The South Asian region greatly contributed to this achievement as it thrives on a continuous economic growth and poverty reduction throughout the decades. However, despite the improvements done throughout the years, the Covid-19 pandemic, and the effects from the war in Ukraine has worsened the situation. Foreign aid is one of the main sources of livelihood for the people for most countries, however the effectiveness of the aid inflow remains questionable as presented, where the quality of governance disrupts the aid distribution to the poor. This study aims to investigate the relationship between foreign aid, governance, and poverty for 8 South Asian countries, namely Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka. The secondary data collected ranges between the year 2000 to 2020 in the form of quantitative data from a secondary source. Quantile regression model is used in this study. The results show that foreign aid and governance both has a direct positive influence on poverty eradication at lower levels of poverty alleviation. At higher poverty alleviation levels, the two variables lose its effect to reduce poverty. Additionally, governance is found to only be effective in moderating aid on poverty eradication when the highest level of poverty eradication is achieved. Therefore, it is crucial for policy makers to understand that improving the quality of governance is not the only way to reduce poverty depending on the level of poverty eradication achievement of the country.